2016
DOI: 10.1167/iovs.15-18434
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Assessment of the Agreement Between Grading of Goniophotographic Images and Gonioscopy in the Chinese-American Eye Study (CHES)

Abstract: PurposeTo compare grading of goniophotographic images and gonioscopy in assessing the iridocorneal angle.MethodsIn a population-based, cross-sectional study, participants underwent gonioscopy and goniophotographic imaging during the same visit. The iridocorneal angle was classified as closed if the posterior trabecular meshwork could not be seen. A single masked observer graded the goniophotographic images, and each eye was classified as having angle closure based on the number of closed quadrants. Agreement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 21 publications
4
35
2
Order By: Relevance
“…Changes in body position induce modest changes in angle dimensions, which may explain the weaker correlations between AS-OCT and EyeCam compared to gonioscopy. 4,5,27 However, previous studies reported fair agreement between gonioscopy and EyeCam in the detection of angle closure, and the correlation results with EyeCam closely resemble our results with gonioscopy; thus, providing cross-validation of our correlation results.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Changes in body position induce modest changes in angle dimensions, which may explain the weaker correlations between AS-OCT and EyeCam compared to gonioscopy. 4,5,27 However, previous studies reported fair agreement between gonioscopy and EyeCam in the detection of angle closure, and the correlation results with EyeCam closely resemble our results with gonioscopy; thus, providing cross-validation of our correlation results.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, previous analysis of CHES EyeCam images found excellent inter- and intraobserver agreement in the detection of angle closure (κ = 0.82 and 0.87, respectively). 4 However, our study has some limitations. First, we are unable to report measures of intra- and interexaminer reproducibility of gonioscopy based on data from CHES.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Agreement levels were also slightly lower overall in comparison to the work of Murakami et al,31 who used the EyeCam instrument for capturing goniophotographs. The difference could be ascribed to a number of reasons, such as image capture technique (slit lamp versus supine position), gaze position (primary versus lens tilt), and the distribution of examined angles (where Murakami et al31 had a cohort with a greater number of closed angles). Our study provides an additional contribution to this discussion by demonstrating that the use of an ordinal scale revealed a conservative grading behavior across graders, which we define as the tendency to grade an angle as narrower than the ground truth, so as to not “miss” a narrow angle 31.…”
Section: Discussioncontrasting
confidence: 58%
“…Gonioscopy is the current clinical standard for evaluating the ACA. EyeCam (Clarity Medical Systems, Pleasanton, CA) is a camera-based assessment method that has been developed and studied as an alternative to gonioscopy 8,9. Quantitative studies of anatomic variation detected by gonioscopy and EyeCam are limited, especially ones that analyze data derived from population-based cohorts.…”
Section: Introductionmentioning
confidence: 99%